The transition to foraging for dense and predictable resources and its impact on the evolution of modern humans - Marean, Curtis W. (Philos Trans R Soc Lond B Biol Sci, 2016)
Scientists have identified a series of milestones in the evolution of the human food quest that are anticipated to have had far-reaching impacts on biological, behavioural and cultural evolution: the inclusion of substantial portions of meat, the broad spectrum revolution and the transition to food production. The foraging shift to dense and predictable resources is another key milestone that had consequential impacts on the later part of human evolution. The theory of economic defendability predicts that this shift had an important consequence—elevated levels of intergroup territoriality and conflict. In this paper, this theory is integrated with a well-established general theory of hunter–gatherer adaptations and is used to make predictions for the sequence of appearance of several evolved traits of modern humans. The distribution of dense and predictable resources in Africa is reviewed and found to occur only in aquatic contexts (coasts, rivers and lakes). The palaeoanthropological empirical record contains recurrent evidence for a shift to the exploitation of dense and predictable resources by 110 000 years ago, and the first known occurrence is in a marine coastal context in South Africa. Some theory predicts that this elevated conflict would have provided the conditions for selection for the hyperprosocial behaviours unique to modern humans. This article is part of the themed issue ‘Major transitions in human evolution’.